Evaluating the invasive plant, Prosopis juliflora in the two initial growth stages as a potential candidate for heavy metal phytostabilization in metalliferous soil. Issue 1 (1st January 2019) - Usman, Kamal; Abu-Dieyeh, Mohammed H.; Al-Ghouti, Mohammad A.
ABSTRACT: Anthropogenic activities leads to increase in toxic metals in the environment. The toxicity of Cd, Cr and Pb to P. juliflora were tested in agar media; Seeds germinated in 25, 50 and 100 mg/L Pb; 5, 10 and 20 mg/ 10 L Cd; and 10 mg/L Cr were mostly unaffected. At 20 and 40 mg/L, Cr inhibited germination. Similarly, Cd and Cr treatments but not Pb disturbed seedlings development. Up to 3366.3 mg/kg and 1228.6 mg/kg of Pb accumulates in the root and shoot. The bioconcentration factor for both tissues ranged from 27.8 to 115.4 and 11.4 to 45.7, respectively. The translocation factor ranged from approximately 0.4 to 0.5, suggesting that it preferentially accumulates Pb in the root. Fourier Transformed Infrared Spectroscopy confirms Pb ions complexation with functional groups on the plant dry tissue biomass. These findings therefore, suggest that P. juliflora is suitable for Pb phytostabilization in metalliferous soil. Abbreviations: ICP-OES: Inductively Coupled Plasma Optical Emission Spectrometry; FTIR: Fourier Transform Infrared Spectroscopy; BCF: Bioconcentration Factor; TF: Translocation Factor.